A tandem queueing system with task-splitting, feedback, and blocking. (15th February 2007) - Haghighi, Aliakbar Montazer; Mishev, Dimitar P.
A novel two-station single-processing tandem queueing system with task splitting, feedback, and blocking is considered. Two cases are analysed: a finite buffer at each station, and only the intermediate buffer finite. After completing processing at each station, a task may leave the system, join the other station, go for split, go to the other station or return to its own station. The steady-state joint distribution of the queue lengths that will lead to the moments of the queue lengths, mean waiting time, probabilities of each station and the system being busy and being idle are obtained through algorithms. A numerical example is provided.